Olhares brancos, terror negro: branquitude e horror em Corra!, de Jordan Peele - HEIDY MAIYUMI RAFAEL KANASIRO (2021)
The present study is aimed to investigate the feature film Get Out, written and directed by Jordan Peele (2017), working on understanding how it builds the horror effect through the representation of whiteness, this option is based on an overview of racial representation in films produced in the United States, later, this study discusses the horror genre in more details. The second section, Representations of Race in American Cinema, appeals to Cultural Studies and Stuart Hall's theory of the Politics of Representation (2016) to think about building processes that pressure the contests whenever the disparities are represented. The main five racial stereotypes in films produced in the United States are discussed, which is entitled in the book Toms, Coons, Mulattoes, Mammies and Bucks: An Interpretative History of Blacks in America Films, Bogle (2016). In return, African American cinema statements are taken and seen as oppositional gazes (hooks, 2019) such as race movies, some productions of the blaxploitation and Spike Lee. The third section focuses on the presence of black people in horror movies and starts with an approach to film genres to understand the structure of the horror genre and its archetypes, amongst horror subgenres, the presence of monsters and their allegorical and repeated use as racial otherness. The third section reviewed the figure of King Kong and its representation as blackness animalization. As a counterpoint to negative stereotyped representations, this study submitted Night of the Living Dead (1968), directed by George Romero, to introduce the concept of whiteness as a dreadful source of horror. In addition are some experiences of animalization and objectification of black people in places of majority of white people, like Fanon, Baldwin, Saartje Baartman review, and among the women who were interviewed by Grada Kilomba referring to the main player in Get Out, Chris. The fourth section holds an assessment from four stretches of Get Out, at first, a study on the character Dean Armitage as an example of the archetype of crazy scientists, the second relates to the position of silencing caused by hypnosis by Missy, the third passage tries to understand the position held by Asian people in race relations from the Hiroki Tanaka's character, at last, the Armitage's mansion will be related to a plantation, associating decolonisation with Chris's gesture when removing the cotton wool out of the ears.